Analysis of Bioaccumulation of Mercury (Hg) in Yuyu Crabs (Parathephusa Convexa) in The Janja River, Malomba Village, Dondo District, Tolitoli Regency - Tri Santoso; Hasrudin Hasrudin; Sitti Aminah; Sri H. V. Pulukadang (Universitas Tadulako, 2025)
The phenomenon of environmental damage due to unlicensed gold mining activities harms aquatic ecosystems. Mercury (Hg) waste from the mining process has the potential to cause bioaccumulation in aquatic biota such as fish and crabs, which can lead to mercury contamination in the human body through the food chain. The bioaccumulation process can also produce toxic organic compounds that harm human health. Therefore, this research aims to determine whether mercury bioaccumulation occurs in yuyu crabs in the Janja River, Malomba Village, Dondo District, Tolitoli Regency, due to gold mining activities. The method used in the research is the calibration curve method with Cold Vapor Atomic Absorption Spectrophotometry (CV-AAS) analysis at a wavelength of 253.7 nm. The results obtained from this research indicate that bioaccumulation has occurred in yuyu crabs that live in the Janja River. The highest accumulated mercury metal levels were obtained at upstream locations with an average of 5.24 ppb; the lowest was in the midstream, which is 1.53 ppb. At the downstream location, it has a mercury concentration of 4.53 ppb. So it shows that the mercury contamination in the yuyu crab samples is below the quality standard threshold, Indonesian National Standard No. 7387 of 2009, for the heavy metal mercury in other types of crabs and crustaceans is 1.0 ppm or 1000 ppb.